Globalization Influence on Alternative Trajectories to Family Formation in Africa - Ayandele, Olusola; Popoola, Olugbenga (My University, 2019)
Family is the most basic institution of society with several socialization functions. Previously, the traditional “normative” family in Africa was a large household made-up of the extended family. Later, globalization processes led to the institutionalization of the nuclear family arrangement as the “typical” married-couple family setting. Currently, the agents of globalization have popularized and made single-parent families (having child/children without being married), and a two-parent cohabiting family (living with one’s partner without being married) lost some social stigma in many African societies. Single-parenthood and cohabitation are becoming “trendy” family structure in many African societies. Guided by the structural functionalism approach, the influence of globalization on the African family structure was discussed. Data from Demographic Health Surveys, World Family Map and various studies from some sub-Saharan African countries were used to examine the prevalence of the married-couple, cohabiting-couple, and single-parent family structures. Since the family is the most prominent family structure in Africa, the society, governmental and non-governmental agencies, education and religious institutions, as well as clinical and social services, should be attuned to the currently diverse “new normal” family systems to ensure that families thrive.
Keywords: Single parents; Cohabitation; Married couple; Globalization; African family